Sulfone adsorption using Fe3+ and Fe6+-impregnated clay adsorbents - Alcaraz, Maegan Gwyneth T. (Animo Repository, 2024)
The reduction of sulfur content from fuel oil is essential for the prevention of sulfur accumulation in the atmosphere, thus, making desulfurization practices necessary. In this study, the adsorption of sulfur, specifically dibenzothiophene sulfone (DBTO) and benzothiophene sulfone (BTO) in the frame of oxidative desulfurization was investigated. Raw bentonite (BR) and raw activated clay (ACR) were impregnated with Fe3+ and Fe6+, creating bentonite-Fe3+ (BF3), bentonite-Fe6+ (BF6), activated clay-Fe3+ (ACF3), and activated clay-Fe6+ (ACF6). The surface functional groups, surface morphology, and surface area of the raw and modified adsorbents were studied through Fourier transform infrared spectroscopy, a scanning electron microscope, and Brunauer-Emmett-Teller analysis, respectively. Batch experiments on simulated oil showed the suitability of the pseudo-second order kinetic model on the clay adsorbent and sulfone system. This suggests that chemisorption is the rate-limiting step of the reaction. Equilibrium isotherms indicated the adherence of DBTO onto BR, and BF3, and BTO onto BF3, and ACR to the Freundlich model. This implies the heterogeneous adsorption of the sulfones onto the adsorbents. The systems of DBTO with BF6, ACR, ACF3, and ACF6, and BTO with BR, BF6, ACF3, and ACF6 showed a better fit with the Dubinin-Radushkevich model. This denotes that adsorption happens through the filling of sulfones of the micropores on the adsorbent. Lastly, thermodynamic studies revealed the endothermic and non-spontaneous nature of the clay adsorbents and sulfone systems. The experiments showed the negative effect of Fe3+ and Fe6+ impregnation on the desulfurization ability of the adsorbents. This could be due to the iron ions being hard acids and the sulfones being soft bases, thus showing lower compatibility than the raw counterparts of the adsorbents. Testing of the adsorbents on oxidized pyrolysis oil yielded around 2% to 3% desulfurization due to the quick saturation of adsorbent capacity because of the high sulfur content of the oil. The experiments revealed BR as the best-performing adsorbent, reaching 60% desulfurization in simulated oil. This study is a step toward the commercialization of alternative desulfurization methods.